2019
DOI: 10.3389/fpsyg.2019.00714
|View full text |Cite
|
Sign up to set email alerts
|

Early Risk Detection of Burnout: Development of the Burnout Prevention Questionnaire for Coaches

Abstract: Introduction: Previous research has shown that burnout develops as the result of a continuous imbalance between chronic stress and appropriate coping resources. Hence, the essential factors to measure burnout encompassed the factors stress and recovery within our studies. However, the Burnout Prevention Questionnaire for Coaches (BPQ-C) does not represent a new questionnaire from scratch, but rather a re-evaluated, condensed, and subsequently combined instrument with scales derived from validated ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…As described above, the BPQ-C should be used for research purposes only at this stage. The correlated residuals in the threefactor structure of the BPQ-C have already been sufficiently argued in the paper (Schaffran et al, 2019) as well as in the manual of the Recovery-Stress Questionnaire (Kallus and Kellmann, 2016). In addition, both the model with and without modifications were presented to allow replication with other data sets.…”
Section: Questionnaire Developmentmentioning
confidence: 67%
See 4 more Smart Citations
“…As described above, the BPQ-C should be used for research purposes only at this stage. The correlated residuals in the threefactor structure of the BPQ-C have already been sufficiently argued in the paper (Schaffran et al, 2019) as well as in the manual of the Recovery-Stress Questionnaire (Kallus and Kellmann, 2016). In addition, both the model with and without modifications were presented to allow replication with other data sets.…”
Section: Questionnaire Developmentmentioning
confidence: 67%
“…The BPQ-C was particularly developed for research interests and is not meant for clinical diagnostics. Moreover, the paper by Schaffran et al (2019) presents a preliminary version of the BPQ-C which has to be confirmed in replication studies containing further samples. Therefore, the present version of the BPQ-C is not suitable for diagnostic-based interventions.…”
Section: Utility As a Screening Toolmentioning
confidence: 99%
See 3 more Smart Citations